Vision health perspectives on Breaking Bad: Ophthalmic sequelae of methamphetamine use disorder - Huang, Ye; Nguyen, Nam V.; Mammo, Danny A.; Albini, Thomas A.; Hayek, Brent R.; Timperley, Brent D.; Krueger, Ronald R.; Yeh, Steven (Frontiers in Toxicology, 2023)
Methamphetamine use has become a rampant public health issue that not only causes devastating consequences to the user but also poses a burden to surrounding communities. A spectrum of ophthalmic sequelae is associated with methamphetamine use and includes episcleritis, scleritis, corneal ulceration, panophthalmitis, endophthalmitis, retinal vasculitis, and retinopathy. In many instances, prompt recognition of the condition and associated infectious process and early initiation of antimicrobial therapy are crucial steps to preventing vision loss. In this review, we summarize the reported ocular complications that may result from methamphetamine use in addition to several postulated mechanisms regarding the ocular toxicity of methamphetamine. The increasing prevalence of methamphetamine use as a public health threat highlights the need for continued investigation of this ophthalmologic issue.